Effectiveness of deep breathing exercise on blood pressure among patients with hypertension - MS.K.SONA JANET,; Dr.P.MANGALA GOWRI, (International Journal of Pharma and Bio Sciences, 2017)
The prevalence for hypertension in India was 29.8% and about 33% urban and 25% rural Indians are hypertensive. In this modern world, stress is increasing in everyone’s life which also a major contributing factor for hypertension. Hypertension can be treated by pharmacological and non-pharmacological methods. Deep breathing exercise is one of the exercise and relaxation technique which helps to decrease the blood pressure and maintain their health in optimal state. The aim of the study is to determine the effectiveness of deep breathing exercise on blood pressure among patients with hypertension. A research design adopted for this study was quasi-experimental design with the sample size of 30 in experimental group and 30 in control group. Sample was selected by using convenient sampling technique. Deep breathing exercise was given for experimental group and control group received the routine care. Their blood pressure was measured by sphygmomanometer before as well as after the intervention in both groups. Data were analyzed by using descriptive and inferential statistics. Deep breathing exercise was found to be effective in reducing both systolic and diastolic blood pressure at the level of p<0.05. The study findings concluded that deep breathing exercise will reduce the blood pressure and improve the quality of life of the patient and also Continuous practicing deep breathing exercise can reduce medicine usage there by it can be used routinely as a complementary method of treatment for hypertension.